posted by .

solve each identity algebraically



  • math -

    my usual approach is to start with the "messy" side, and change everything to sines and cosines.

    =(1- sinx/cosx)/(1 - cosx/sinx)
    = (cosx-sinx)/cosx * (sinx)/ (sinx - cosx)
    = (-1)sinx/cosx
    = -tanx

    perform similar steps for the second one, bet you'll get it

  • math -

    I got (1- sinx/cosx)/(1 - cosx/sinx)
    but how did (1- sinx/cosx) turn to (cosx-sinx)/cosx?

  • math -

    nevermind, found out :) thanks

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 vibrations per second, write an equation in the form d=sinw(t) for the simple harmonic motion. 2) Verify the identity tan^2X-cot^2X/tanX+cotX=tanX-cotX I'm not …
  2. Pre-Calc

    How do I solve this? My work has led me to a dead end. tan(45-x) + cot(45-x) =4 my work: (tan45 - tanx)/(1+ tan45tanx) + (cot45 - cotx)/(1 + cot45cotx) = 4 (1-tanx)/(1+tanx) + (1-cotx)/(1+cotx) = 4 Then I found a common denominator,
  3. Trig

    Verify that each of the following is an identity. tan^2x-sin^2x=tan^2xsin^2x I can get it down to cos^2 on the right, but cannot get it to work out on the left. secx/cosx - tanx/cotx=1 On the left I got down to 1-tan^2, but that clearly …
  4. trig

    verify the identity: tan^2x(1+cot^2x)=1/1-sin^2x Verify the Id: tanx + cotx/ tanx-cotx = (1/sin^2x-cos^2x)
  5. trig

    verify the identity (tanx+cotx) (1) __________ = ______________ (tanx-cotx) (sin^2x-cos^2x)
  6. trigonometry

    tanx-cotx/tanx+cotx=1-2cos squardx
  7. calculus

    1/tanx + 1/cotx =tanx +cotx verify
  8. matj

    prove that (cotx+tanx)(cotx-tanx) = 1/(sin^2 x) - 1/(cos^x)
  9. trig

    Verify the trigonometric identity. Please show all steps. tanx-cotx/tanx+cotx=sin^2x-cos^2x
  10. a math

    Prove cotx-1/cotx+1 = sec2x - tan2x I prove till cotx-1/cotx+1 =1/1+tanx - tanx/1+tanx

More Similar Questions